Prácticas profesionales: una mirada desde la evaluación por competencias (Educational Perspectives Magazine (REPED), 2023)
Within the context of the School of Education for Preschoolers of Central University, it has been proposed the evaluation of the students during their professional practice period , including the incorporation of a model focused in the development of competencies competitions, reason by which varied actions have been designed to complement this process from the diverse requirements determined by each of the lines of the graduation competencies .The successful advance has been stated, in relation to the model used previously, being able to realize an evaluation that contemplates the dimensions of each one of the competences to manage, using different strategies where the students can demónstrate these competences, achieving a clear process and realize a good teamwork incorporating the students in it.That is why it is important to consider that the information delivered through this way of evaluation, allows us to visualize what it is the really possible to demónstrate, in agreement to the occupation and own dynamics of what is happening nowadays, within the Preschoolers Education; aspect at that invites you to look from the concrete experience of the students, the coherence existing between the offers of vocational training on the basis of competences and the reality of each one of the institutions and the classrooms compromised inside this process.
Keywords: Pedagogic practices, Evaluation based on competences.